Dentists' perception of the Role they play in early detection of oral cancer - Saleh, A.; Kong, Y.H.; Vengu, N.; Badrudeen, H.; Zain, R.B.; Cheong, S.C. (2014)
Background: Dentists are typically the first professionals who are approached to treat ailments within the oral cavity. Therefore they should be well-equipped in detecting suspicious lesions during routine clinical practice. This study determined the levels of knowledge on early signs and risk factors associated with oral cancer and identified which factors influenced dentist participation in prevention and early detection of oral cancer. Materials and Methods: A survey on dentists’ knowledge and their practices in prevention and early detection of oral cancer was conducted using a 26-item self-administered questionnaire. Results and Conclusions: A response rate of 41.7% was achieved. The level of knowledge on early signs and risk habits associated with oral cancer was high and the majority reported to have conducted opportunistic screening and advised patients on risk habit cessation. Factors that influenced the dentist in practising prevention and early detection of oral cancer were continuous education on oral cancer, age, nature of practice and recent graduation. Notably, dentists were receptive to further training in the area of oral cancer detection and cessation of risk habits. Taken together, the study demonstrated that the dental clinic is a good avenue to conduct programs on opportunistic screening, and continuous education in these areas is necessary to adequately equip dentists in running these programs. Further, this study also highlighted knowledge deficits and practice shortcomings which will help in planning and developing programs that further encourage better participation of dentists in prevention and early detection of oral cancer.